Wybrane uwagi na temat kapitału - Wrońska, Elżbieta Maria (Some Comments on Capit, 2007)
This article refers to capital management. There is not one commonly accepted definition of capital. The capital can be understood as the sum of liabilities and shareholders' equity and equals the value of the left - hand side of balance sheet i.e. assets. There is also another meaning of the capital - it can be perceived as the sum of the long-term liabilities and shareholders' equity. The definition of capital should concern the shareholder's equity and liabilities gained from capital market. It means that only some accounting information shown in right - hand side of balance sheet can be treated as the capital. Only owners' equity, long term debt and notes payable may be sum up to fix the amount of the capital. The accounts payable should not be included in capital because they come from goods market.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1152, s. 648-655